IMPROVING STUDENT LEARNING OUTCOMES IN LEARNING IPA USING THE EXPERIMENTAL METHOD SD WEST PASAMAN - NAULIA, RESKI (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This researche was started from  the fact at SDN 05 Sungai Aur in which the learning was dominated by teacher as information source. The researcher used qualitative and quantitative approaches which consist of two cycles involved four phases which is planning, implementation, observation, and reflection. The subjects were teacher, researcher and twenty three grade IV students. The result of researche showed improvement. The improvement was involved a) the lesson plan in the first cycle had percentage 74 % (enough) increase to 85,5% (good) in the second cycle. b) the implementation of teacher`s aspect in the first cycle was 78% (good) increased to 86% (very good)  in the second cycle. c) the implementation of students` aspect was 71,5% (good) in the first cycle increased to 87% (very good). Then, the outcome of students learning in the first cycle was 68,07% (enough)  increased to 79% (good) in the second cycle. Thus, it can be concluded that experiment method able improve outcome of student learning in science learning in grade IV SDN 05 Sungai Aur.   Kata Kunci: hasil, belajar, ipa,  metode,  eksperimen, SD